2015
DOI: 10.1519/jsc.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Laboratory vs. Field Testing of Peak Power, Torque, and Time of Peak Power Production Among Elite Bicycle Motocross Cyclists

Abstract: The aim of this study was to ascertain the variation in elite male BMX cyclists' peak power, torque and time of power production during laboratory and fieldbased testing. Eight male elite BMX riders volunteered for the study and each rider completed 3 maximal sprints using both an SRM ergometer in the laboratory, and a portable SRM power meter on an Olympic standard indoor BMX track. The results revealed a significantly higher peak power (p = < 0.001, 34 ± 9 %) and reduced time of power production (p = < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Bertucci's study showed that 32% higher force was applied to the bicycle during standing sprints, when compared to seated sprints. Similar findings were reported in a study that compared laboratory sprints on a cycle ergometer to sprints performed on a BMX track when riders used their own bikes (16). Rylands et al (2015) concluded that the laboratory cycle ergometer restricted the natural lateral oscillation of the bicycle and resulted in a mean reduction in power of 34 %.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…Bertucci's study showed that 32% higher force was applied to the bicycle during standing sprints, when compared to seated sprints. Similar findings were reported in a study that compared laboratory sprints on a cycle ergometer to sprints performed on a BMX track when riders used their own bikes (16). Rylands et al (2015) concluded that the laboratory cycle ergometer restricted the natural lateral oscillation of the bicycle and resulted in a mean reduction in power of 34 %.…”
Section: Introductionsupporting
confidence: 64%
“…Similar findings were reported in a study that compared laboratory sprints on a cycle ergometer to sprints performed on a BMX track when riders used their own bikes (16). Rylands et al (2015) concluded that the laboratory cycle ergometer restricted the natural lateral oscillation of the bicycle and resulted in a mean reduction in power of 34 %. Both of these studies confirmed that the oscillation of a BMX bicycle is only possible when a rider is pedalling, as the movement is used as leverage by the upper body (1,16).…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Prior to testing each rider completed a 10 minute familiarisation session and self-paced warm up. Specifically, each rider carried out their standard pre-competition routine, which included seated cycling, and a series of short standing sprints (Rylands, Roberts & Hurst 2015a). Participants performed the warm up using the standard race gear ratio (43/16) on their own bikes.…”
Section: Experimental Designmentioning
confidence: 99%